Contrasting Inflammatory Signatures in Peripheral Blood and Bronchoalveolar Cells Reveal Compartment-Specific Effects of HIV Infection - Muema, Daniel M.; Mthembu, Maphe; Schiff, Abigail E.; Singh, Urisha; Corleis, Björn; Chen, Dongquan; Bassett, Thierry; Rasehlo, Sipho S.; Nyamande, Kennedy; Khan, Dilshaad Fakey; Maharaj, Priya; Mitha, Mohammed; et al. (Frontiers in Immunology, 2020)
The mechanisms by which HIV increases susceptibility to tuberculosis and other respiratory infections are incompletely understood. We used transcriptomics of paired whole bronchoalveolar lavage cells (BLCs) and peripheral blood mononuclear cells to compare the effect of HIV at the lung mucosal surface and in peripheral blood. The majority of HIV-induced differentially expressed genes (DEGs) were specific to either the peripheral or lung mucosa compartments (1,307/1,404, 93%). Type I interferon signaling was the dominant signature of DEGs in HIV-positive blood but not in HIV-positive BLCs. DEGs in the HIV-positive BLCs were significantly enriched for infiltration with cytotoxic CD8+ T cells. Higher expression of type 1 interferon transcripts in peripheral CD8+ T cells and representative transcripts and proteins in BLCs-derived CD8+ T cells during HIV infection, including IFNG (IFN-gamma), GZMB (Granzyme B) and PDCD1 (PD-1), was confirmed by cell-subset specific transcriptional analysis and flow cytometry. Thus, we report that a whole transcriptomic approach revealed qualitatively distinct effects of HIV in blood and bronchoalveolar compartments. Further work exploring the impact of distinct type I interferon programs and functional features of CD8+ T cells infiltrating the lung mucosa during HIV infection may provide novel insights into HIV-induced susceptibility to respiratory pathogens.